Judicialização do acesso à saúde pública: itinerários e experiências de usuários - Irber, Ana Paula Silva Fernandes (Universidade Federal Rural do Semi-Árido, 2020)
The judicialization of health is a complex social phenomenon in the context of guaranteeing rights, with financial and administrative impacts on the Brazilian public system. The increase in the number of actions in recent years signals challenges and obstacles for the Unified Health System (SUS) regarding the effectiveness of its fundamental principles and guidelines, especially access to health care by the population. The present study aims to analyze the profile of judicial demands, the experiences and the itineraries of users who accessed the judicial route to guarantee health care. This is a descriptive and documentary study, with a quantitative and qualitative approach. In the documentary stage, a survey of the profile of lawsuits in health matters was carried out based on data from the Attorney General's Office of the Municipality of Mossoró-RN (PGM-MOS) that were processed in the 13th federal court (Federal Special Court) in the period from 2017 to 2019. In the field stage, semi-structured interviews were carried out with ten users who resorted to the judicial system to guarantee health care in the local SUS, selected through a search of the database obtained from the PGM-MOS. The treatment and analysis of quantitative findings was done with the support of Microsoft Excel® software (version 2007), through simple statistical treatment; and, in qualitative findings, Bardin's thematic content analysis technique was used. As a result, it was observed that most of the actions were proposed by women (53.00%), aged between 20 and 59 years (53.91%), occupation among retirees, pensioners and beneficiaries of aid (18.43%), with the majority residing in the Abolição, Santo Antônio and Barrocas neighborhoods. Regarding the nature of the action, they were all of an individual nature and proposed by individuals. The predominant pathology among the processes was orthopedic trauma (33.04%), with surgeries being the most required health asset (45.39%) with emphasis on bone (65.9%). As for the origin of professional prescription, there was a predominance of the private network (61.57%). The main legal representation was the Public Defender (66.26%). As for the socioeconomic profile of the participants, the majority were female, with a family income of one minimum wage and as a level of education, they declared complete high school. The testimonies of users who resort to the judicial system to access treatment in the SUS revealed itineraries marked by the surprise of the diagnosis of the disease until the search and denial of access to treatment, in a complex process of paths taken between services and public agencies. The judicial route has emerged as the main alternative in the fight for the guarantee of the right to health within the scope of SUS, either as a guiding resource for equity in access, with the dispensation of the desired treatment; or even, in the negative desolate, in cases where the requested request was unsuccessful. In this context, it is identified that the users' experiences point out the obstacles and obstacles experienced during the judicialization process, in a mix of feelings such as disappointment with the public health system, joy of having their right guaranteed or even discontent with the Brazilian State. . The need for actions in the field of public policies aimed at improving access to health care is recognized, with a view to expanding and equitable distribution of resources for financing and structuring the SUS
Keywords: Direito à Saúde; Judicialização da Saúde; Saúde Pública; Sistema Único de Saúde; Right to Health; Health Judicialization; Public health; Health Unic System; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES